Keputusan Kunjungan Wisata Ngungun Saok Yang Dipengaruhi Oleh Green Marketing dan E-WOM - Rahim , Hamidah (CV. ITTC INDONESIA, 2023)
The research was done in Ngugun Saok Lubuk Minturun aimed at to investigate the influence among variables green marketing, and e-wom on the variables of decision visit tourism objects in Ngungun Saok. The model of the research uses quantitative . A values that is green marketing, and e-wom as the independent variable and decisions visit as dependent variable. A population that is used all visitors tourism objects in Ngungun Saok on December 2022 with samples from 95 people. The determination use random sample of sampling. The result of the research show significance value of green marketing is 0,002, and e-wom is 0,172. So that variable green marketing significant its impacts to decision visit, while e-wom influential insignificant of the decision visit in Ngungun Saok.